Prophylactic Phenylephrine Increases the Dose Requirement of Oxytocin to Treat Uterine Atony During Cesarean Delivery: A Double-Blinded, Single-Center, Randomized and Placebo-Controlled Trial - Shen, Yao-Hua; Yang, Fan; Jin, Li-Dan; Qian, Yu-Jia; Xing, Li; Huang, Ya-Li; Lin, Su-Feng; Xiao, Fei (Frontiers in Pharmacology, 2021)
Purpose: Murine studies have shown that phenylephrine inhibits uterine contractions in non-pregnant mice through cyclic adenosine monophosphate (cAMP) signaling. However, there has been no limited exploration to date of the effect of phenylephrine on uterine contractions in clinical practice. This study aimed to compare the dose requirement of oxytocin with or without the infusion of prophylactic phenylephrine to prevent post spinal hypotension during cesarean delivery under combined spinal and epidural anesthesia. Methods: This is a double-blinded, single-centre, randomized, control study. One hundred and sixty pregnant patients provided informed consent and were randomly allocated to the intervention (phenylephrine infusion) and control (saline infusion) groups. Patients randomised to the intervention received a prophylactic phenylephrine infusion intravenously at a fixed rate of 0.5 μg/kg/min. The control group received a saline placebo at the same rate, and used the same apparatus for delivery. After neonatal delivery and clamping of the umbilical cord, patients received intravenous oxytocin in accordance with the “Rule of Threes” protocol to prevent uterine atony. The primary outcome measure was the total dose of oxytocin administered during CD. Secondary outcomes including the percentage of patients requiring a secondary uterotonic agent, estimated blood loss (EBL) in the first 24 hours after surgery. Results The median oxytocin dose administered was significantly higher in the phenylephrine group than in the control group (6.9 ± 2.5 international standardised units (IU) vs. 5.4 ± 2.4 IU, P = 0.0004). The number of patients that required a secondary uterotonic agent was significant higher in phenylephrine group than in control group (24.2% vs. 9.1%; P = 0.034). The EBL in first 24-hours postoperatively was similar between the two groups (467 ± 47 ml vs. 399 ± 38 ml; P = 0.26). Conclusions Prophylactic infusion of phenylephrine used to prevent post-spinal hypotension during CD increased the dose of oxytocin required to prevent uterine atony. This has important clinical implications, as the suboptimal use of oxytocin is associated with an increased risk of postpartum hemorrhage and increased maternal morbidity and mortality. Further studies are needed to confirm these findings.